Identification of Differentially Expressed Proteins in Serum of Obese Patients by Isobaric Tags for Relative and Absolute Quantification (iTRAQ)-Coupled 2D LC-MS - Zhang, Ying; Chen, Zhong; He, Yue; Wang, Jianxia; Jiang, Minhui; Xu, Jianjuan; Chen, Minghua; Feng, Yaling (Medical science monitor, 2020)
BACKGROUND The aim of this study was to identify the differentially expressed proteins of obese patients compared with normal participants and to provide a potential target for future investigation of obesity. MATERIAL AND METHODS We enrolled 10 obese male adults and 10 matched normal subjects. Serum samples were collected to get total protein extraction, denaturation, deoxidation, and enzymatic hydrolysis. Differentially expressed proteins were distinguished with mass spectrometry after samples were labeled with iTRAQ. RESULTS A total of 9622 differentially expressed peptides were identified, corresponding to 733 proteins; 118 proteins of these showed significant differential expression, with 15 upregulated and 103 downregulated. CONCLUSIONS iTRAQ is an effective technique to identify differentially expressed proteins in obese patients. The development of obesity is correlated with a series of complex elements and mutual effects. The proteins identified in this study may provide novel directions and targets for future pathological studies of obesity.